Залишки обряду сепарації в епічних піснях про весілля - Петкович, Д. (Народна творчість та етнологія, 2012)
This paper deals with the ritual background of the epic poems about the marriage, particularly the first segment of the rites of passage – the separation. Poems about marriage, as «male text», are focused on the male liminal phase and female separation. In the epic pattern, the fragments of the ritual practice are retained, modified, emphasized, or excluded, moved on the linear axis as provided by the logic of the epic genre.